O Manicômio Judiciário: saúde ou justiça? The Judiciary Mental Hospital: a question of health or of law? - Evelin Naked de Castro Sá (Universidade de São Paulo, 1985)
O Manicômio Judiciário, por ser um hospital-presídio, pode estar subordinado tanto à Secretaria da Saúde como à Justiça. Como elementos de análise dessa decisão, são apresentadas comparações estruturais e de recursos humanos entre o Manicômio Judiciário e a Penitenciária de Araraquara, entre a situação de recursos humanos do Manicômio em 1981 e 1984 e entre os salários de algumas funções de servidores ligados àqueles tipos de instituições. As conclusões apontam a Secretaria da Justiça como a mais adequada para subordinar o Manicômio Judiciário, desde que tomadas algumas medidas de modernização organizacional. É sugerido um quadro de pessoal estruturado percentualmente por subgrupos de funções. As propostas relativas ao pessoal necessitam ser tratadas em leis complementares que garantam, por sua hierarquia, o atendimento das condições excepcionais de trabalho do Manicômio Judiciário. As the Manicômio Judiciário (a Judiciary Mental Health Hospital) is a hospital-prison it could be subordinated either to the State Health Department or to the Department of Justice. In order to reach a sound decision regarding this issue, structural and human resource comparisons as between the Manicômio Judiciário on one side and the Araraquara Prison on the other are provided. Comparisons between the status of the human resources of the Manicômio Judiciário in 1981 and 1984 and between the wages earned by workers exercising similar functions and belonging to similar institutions are also presented. The conclusion points to the Department of Justice as the most adequate institution to which the Manicômio Judiciário should be subordinated, provided some up-to-date managerial measures are taken. A personnel chart is suggested, showing percentages of people organized according to subgroups of functions. The proposals regarding personnel must be dealt with by, supplementary laws which guarantee, adequate provision for the excepcional working conditions prevailing in the Manicômio Judiciário according to position of the staff in the hierarchy.